2014
DOI: 10.1097/gox.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Excision of Non–Melanoma Skin Cancer in an Elderly Veteran’s Affairs Population

Abstract: Background:Non–melanoma skin cancer (NMSC) is the most common malignancy in the United States. Recommended treatment for NMSC remains surgical excision following a positive biopsy. Evidence of complete spontaneous regression of residual NMSC exists in the case of small lesions macroscopically removed by shave biopsy, but with a positive microscopic margin. The present study investigates the rate at which residual tumor is present at subsequent excisional biopsy, with the aim to assess if recommendation to forg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Stewart et al 49 assessed elderly patients with KCs thought to be small enough for complete removal by shave biopsy. Examination of the surgical specimens taken after shave biopsy showed that 42% of the BCC specimens and 73% of the cSCC specimens were negative for residual tumour.…”
Section: Effect Of Age On Treatment Outcomes Of Common Treatment Modamentioning
confidence: 99%
“…Stewart et al 49 assessed elderly patients with KCs thought to be small enough for complete removal by shave biopsy. Examination of the surgical specimens taken after shave biopsy showed that 42% of the BCC specimens and 73% of the cSCC specimens were negative for residual tumour.…”
Section: Effect Of Age On Treatment Outcomes Of Common Treatment Modamentioning
confidence: 99%
“…The current literature suggests that the treating physician’s specialty could also affect the technique utilized. For example, while some dermatology articles suggest that tangential shave removal of certain lesions provides an acceptable cure rate, Stewart et al found an unacceptably high rate of residual BCC and SCC after shave biopsies [ 114 , 116 ]. This reflects the controversy surrounding type of biopsy employed previously in this article.…”
Section: Treatment Of Nmsc: Overview Of Surgical and Non-surgical mentioning
confidence: 99%
“…Oftentimes, no residual carcinoma is detected, implying spontaneous clearance at rates reported to vary from 24% to 76%. [2][3][4][5] These types of lesions have been investigated by others 2-5 and are not fully understood. Our study aims to determine the lesion and patient characteristics that would most strongly predict a histologically negative result for an excised lesion after a biopsy specimen had positive margins.…”
Section: Analysis Of Cases In Which a Biopsy Specimen Is Positive Andmentioning
confidence: 99%
“…However, generalizability of these outcomes to underserved patients may be hindered by unrecognized barriers. 2 The aim of this study was to identify patient-reported barriers to successful implementation of a preoperative risk-reduction program at a safety-net hospital.…”
Section: Barriers To Participation In Preoperative Risk-reduction Promentioning
confidence: 99%